Electromagnetic vibration and noise analysis of permanent magnet synchronous motor with different slot‐pole combinations. Issue 9 (1st November 2016) - Lin, Fu; Zuo, Shuguang; Wu, Xudong
Abstract : This study first employs Maxwell stress tensor method to derive the spatial and temporal distribution characteristics of radial force which induces the electromagnetic vibration and noise. 2D fast Fourier transform is adopted to obtain the frequency components of radial force with specifically spatial harmonic order and force harmonics in six motors with different slot‐pole combinations are compared. Then, a multiphysics model for electromagnetic vibration and noise prediction considering the non‐uniformly distributed force on the teeth surface is established. Mode superposition method and boundary element method are, respectively, used to calculate the stator vibration and noise. The vibration and noise level in motors with different slot‐pole combinations are compared and the corresponding field harmonic sources of noise peaks are located based on 2D decomposing of radial force. Finally, the noise level under different rotational speed and current is discussed. It is mainly concluded that the lowest spatial order force dominates the vibration and noise performance. The noise level under different rotational speed and current depends on the amplitude and frequency of the lowest order force which is the closest to the frequency of the stator mode with the same spatial order.